How Are Infants Suspected to Have Cow's Milk Allergy Managed? A Real World Study Report - Vandenplas, Yvan; Belohlavkova, Simona; Enninger, Axel; Frühauf, Pavel; Makwana, Niten; Järvi, Anette (Nutrients, 2021)
The purpose of this study was to evaluate the diagnosis and management of infants presenting with symptoms attributable to cow's milk allergy (CMA) in a real life setting and to test how the Cow's Milk-related Symptom Score (CoMiSS®) can be used to support the awareness to diagnose cow's milk protein allergy in primary care practice. The CoMiSS is an awareness tool based on various symptoms such as crying, gastrointestinal symptoms, dermatological and respiratory symptoms. The study was conducted on 268 infants from four countries (Belgium, Czech Republic, Germany, UK) aged 0 to 18 months consulting for CMA related symptoms. The analysis was based on two visits of these subjects. The results show an average CoMiSS of 11 at the first visit. After a therapeutic dietary intervention, the score at the second visit, which happened 3 weeks ± 5 days after the first one, dropped to an average value of 4. A satisfaction questionnaire completed by the primary care practitioners suggested an overall high level of satisfaction with the application of the CoMiSS tool in routine practice. These data highlight a huge discrepancy in the diagnosis and management of infants suspected of CMA in the different countries. The findings suggest that the CoMISS questionnaire is an effective tool in aiding awareness of CMPA in primary health care.
Keywords: Surveys and Questionnaires; novorozenec; Infant, Newborn; Infant; Humans; primární zdravotní péče; Belgium; kojenec; Allergens; alergie na mléko; mléčné bílkoviny; Primary Health Care; Female; Spojené království; alergeny; lidé; zvířata; amino acid formula; Germany; Milk Hypersensitivity; Německo; průzkumy a dotazníky; United Kingdom; extensive hydrolysate; Belgie; ženské pohlaví; Male; Milk; Czech Republic; cow’s milk allergy; Milk Proteins; Animals; Česká republika; mužské pohlaví; prospektivní studie; partial hydrolysate; mléko; CoMiSS; Prospective Studies